Copy Move Forgery Detection - Ritu Agarwal, Himanshu Jain, Kunal Raj, Ayush Singh (International Journal of Advanced Science and Technology, 2020)
Copy-move forgery is used for hiding the truth. Detection of forgery by this type of attack is one of the most examined topics currently. This type of forgery is very easy to use because of which its popularity is increasing at a very high rate. Furthermore, detection of such forgery is very difficult as the features between the original and the manipulated image are essentially the same because the source of copied patch is from the original image. In this paper, we bring a technique to detect forgery by such type of attack in images with a model and adjusting it to reduce features in order to improve efficiency while maintaining/ improving the accuracy of detection.